Soft-sediment deformation structures in the late Miocene Selmo Formation around Adiyaman area, Southeastern Turkey - Tasgin, Calibe Koc; Orhan, Hukmu; Turkmen, Ibrahim; Aksoy, Ercan (Elsevier, 2011)
The Selmo Formation was deposited in the basins associated with the Southeastern Anatolian Thrust Belt and East Anatolian Fault Zone in SE Turkey. These structures developed as a result of compressional stresses created by the movement of the Arabian plate to the north and the Eurasian plate to the west from early Miocene to late Pliocene. The outcrops of the Selmo Formation in the Adyyaman area (SE Turkey) comprise braided river deposits (lower alluvial unit) at the base, lacustrine and deltaic deposits in the middle (lacustrine unit) and low sinuousity river and alluvial deposits at the top (upper alluvial unit). Soft-sediment deformation structures were developed in sandstone, siltstone and marl of the deltaic and lacustrine unit of the Selmo Formation. These are slumps, recumbent folds, load casts, ball-and-pillow structures, flame structures, neptunian dykes, chaotically associated structures and synsedimentary faults. The tectonic setting of the basin, the lateral extent of the soft-sediment deformation structures over tens of kilometers, their similarities to deformation structures interpreted as being induced seismically in other regions worldwide or in a laboratory setting, and being confined by undeformed layers suggest that the main trigger system was related to seismic activity in the area. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Soft-sediment deformation structures; Selmo Formation; Lacustrine and deltaic sediments; Southeastern Anatolian Thrust Belt; Adyyaman